Placentophagy: What Should Nurses Recommend?. Issue 2 (March 2018) - Killion, Molly M.
Abstract : There is a small but growing trend of women asking for their placenta after giving birth so they can have it prepared for ingestion during the postpartum period. Our maternity nursing expert, Molly Killion, explains what you need to know about placentophagy so you can offer evidence-based guidance to women who may have this request.